Effect of Jin's Three Needles Therapy Combined with Mirror Therapy on Lower Limb Dysfunction with Cerebral Infarction Patients: Analysis Based on Surface Electromyography - XU Mingzhu, LIN Run, WEN Huaneng, WANG Yixiao, LIU Lu, WANG Bihan, CHEN Kexun, XUAN Chunyu, CUI Shaoyang (Zhongguo quanke yixue, 2023)
Background Cerebral infarction often leads to lower limb motor dysfunction and reduces patients' quality of life. Previous studies have shown that acupuncture combined with mirror therapy can improve lower limb dysfunction in patients with cerebral infarction, but there are few studies and the evaluation methods need to be supplemented. Objective To analyse the clinical efficacy of Jin's three needles therapy combined with mirror therapy in the treatment of lower limb dysfunction in patients with cerebral infarction based on surface electromyography (sEMG) . Methods Ninety lower limb dysfunction with cerebral infarction patients in the Department of Rehabilitation Medicine and the Department of Neurology of Shenzhen Hospital of Southern Medical University from July to December in 2022 were selected as the study subjects and divided into the Jin's three needles therapy group, mirror therapy group and Jin's three needles therapy combined with mirror therapy group. Patients in all three groups received basic treatment, Jin's three needles therapy was added to the Jin's three needles therapy group, knee mirror training was added to the mirror therapy group, and the Jin's three needles therapy and knee mirror training were both added to the Jin's three needles therapy combined with mirror therapy group. All three groups were treated once/d, 5 times/week, for a total of 4 weeks. sEMG was used to evaluate the function of the lower limb muscle and nervous system of the affected side before and after treatment, including time-domain index〔root mean square (RMS) 〕 and frequency-domain index〔median frequency (MF) 〕. Lower limb motor function was assessed using the Fugl-Meyer Assessment-Lower Extremity (FMA-LE) . Results There was no statistically significant difference in the scores of RMS and MF of biceps femoris, anterior tibial muscle, rectus femoris and gastrocnemius muscle in the affected side after 4 weeks of treatment between the mirror therapy group and the Jin's three-needle therapy group (P>0.05) . The scores of RMS and MF of biceps femoris, anterior tibial muscle, rectus femoris and gastrocnemius of the affected side after 4 weeks of treatment in the Jin's three-needle therapy combined with mirror therapy group were higher than those in the Jin's three needles therapy and mirror therapy group (P<0.05) . The FMA-LE scores of patients after 4 weeks of treatment in the Jin's three needles therapy combined with mirror therapy group were higher than those in the Jin's three-needle therapy and mirror therapy groups (P<0.05) . Conclusion Compared with the Jin's three-needle therapy or mirror therapy, Jin's three-needle therapy combined with mirror therapy can more effectively improve the lower limb muscle nervous system function and motor function of patients with cerebral infarction.